Bird Diversity in Paddy Field Habitats During The Paddy Ripening Phase (Oryza sativa L.) Jurong Peujeura Village, Aceh Besar Regency, Indonesia - Mardiana Putri; Aida Fithri Fithri; Zuriana Siregar (The International Journal of Tropical Veterinary and Biomedical Research, 2023)
Birds are organisms that can be found in a variety of habitats. One of the bird habitats is paddy fields. Birds found in paddy fields generally carry out activities such as foraging, breeding, and competing. This study aims to determine the diversity of birds in paddy field habitats during the paddy ripening phase (Oryza sativa L.). The study was conducted from April to June 2022. The location of the study was Jurong Peujera Village, Ingin Jaya District, Aceh Besar Regency. This study used the Point Count method with a radius of 50 m and a distance between points of 150 m. Observations were made at 9 observation points with 4 repetitions, in which the duration of observations was 10 minutes at each observation point. The observation was conducted in the morning and evening at 06.30-10.00 AM and 03.30-05.00 PM. The results obtained were 2586 bird individuals consisting of 14 species from 11 families. The species with the highest number of individuals are Lonchura punctulata with 1535 individuals and Bubulcus ibis with 637 individuals. The highest percentage of families by species is Ardeidae (22%), and Estrildidae (15%). The Shannon-Wiener bird species diversity index in the paddy field area during paddy ripening phase was obtained H'=1.24 which indicates the level of diversity of the bird species is moderate. Meanwhile, based on the dominance index, Simpson shows a value of C=0.42 which indicates a low bird dominance level. The low level of bird dominance is due to the moderate diversity of species in the paddy field area.